Effects of Zn, Mg and Cu Doping on Oxidation Reaction of Al (111) Surface - Ji, Hua; Ren, Keliang; Yang, Jia; Zhang, Yating; Wang, Guan (Frontiers in Chemistry, 2022)
Aiming at the performance degradation of lithium-ion batteries due to shell corrosion, the doping of alloy elements Zn, Mg and Cu on Al(111) surface and the effect on oxidation reaction of Al(111) surface were studied by the first-principles calculation method based on density functional theory. The results show that Zn, Mg and Cu atoms stably combine with Al atoms, and the surface smoothness is slightly different due to their different radii and electronic properties. The dissociative adsorption of O2 molecules is related to the surface doping atoms and O2 coverage, while the electron tunneling of underlying metal promotes O2 adsorption. At the same time, the O atoms adsorbed on the hcp site gradually migrate to the subsurface layer. Zn, Mg, Cu and vacancy defect hinder the migration of the surrounding O atoms to subsurface layer, resulting in different structures and thicknesses of the oxide film near the doped atoms. Zn, Mg, and Cu atoms differ in their ability to gain or lose electrons resulting in their different positions on the surface. In addition, the surface work function rises with the increase of O2 coverage, and Zn and Cu atoms make the work function increase faster.